Mechanical properties and fracture dynamics of silicene membranes - Botari, Tiago; Perim, Eric; Autreto, P. A.S.; Paupitz, Ricardo [UNESP]; Galvao, Douglas S. (Springer Nature, 2013)
The advent of graphene created a new era in materials science, Graphene is a two-dimensional planar honeycomb array of carbon atoms in sp 2-hybridized states. A natural question is whether other elements of the IV-group of the periodic table (such as silicon and germanium), could also form graphene-like structures. Structurally, the silicon equivalent to graphene is called silicene. Silicene was theoretically predicted in 1994 and recently experimentally realized by different groups. Similarly to graphene, silicene exhibits electronic and mechanical properties that can be exploited to nanoelectronics applications. In this work we have investigated, through fully atomistic molecular dynamics (MD) simulations, the mechanical properties of single-layer silicene under mechanical strain. These simulations were carried out using a reactive force field (ReaxFF), as implemented in the LAMMPS code. We have calculated the elastic properties and the fracture patterns. Our results show that the dynamics of the whole fracturing processes of silicene present some similarities with that of graphene as well as some unique features. © 2013 Materials Research Society.